Comprehensive chemical profiling and human health risk assessment of potentially toxic heavy metals in some traditional herbal concoctions from Botswana - Phiri, Ontlametse H. E.; Lepodise, Lucia M.; Pheko-Ofitlhile, Tshepo (Frontiers in Pharmacology, 2025)
Traditional herbal mixtures are still used extensively in Botswana because of their claimed therapeutic benefits, although their chemistry and safety are undocumented. Therefore, this study aims to conduct the analysis and human health risk assessment of some herbal concoctions in Botswana. The spectra of the herbal concoction samples sourced from three different street vendors were recorded at room temperature using the Fourier Transform Infrared (FT-IR) technique. The three samples exhibited comparatively similar spectral profiles, indicating that they may contain chemical compounds vibrating at similar energies. FT-IR analysis revealed the presence of characteristic functional groups which includes phenolics, alcohols, alkene, alkanes and aromatic groups some of which were identified through gas chromatography–mass spectrometry (GC-MS) analysis. GC-MS analysis of all the hexane extracts identified octane and 3-methylheptane as the major constituents. Hexadecane, tetradecane and 5-Aminovaleric acid were major compounds identified in ethyl acetate extracts. Inductively Coupled Plasma Optical Emission Spectrometer (ICP-OES) results revealed that the heavy metal concentrations of herbal concoctions that ranged between 1.00 × 10−4 mg/kg and 2.43 × 101 mg/kg. The concentrations of all the heavy metals were below the acceptable limits set by World Health Organization (WHO). Trace metal concentrations of Mg, Ca, K and Na in the samples ranged from 1.31 × 10−1 to 2.79 × 101 mg/kg, 4.34 × 10−1 to 2.36 × 102 mg/kg, 1.13 to 2.26 × 101 mg/kg and 3.08 × 10−1 to 5.07 × 101 mg/kg respectively. The human health risk analysis showed that there was no potential health risk associated with the consumption of the herbal concoctions and As concentration levels in sample A requires close scrutiny. These findings provide valuable information on the chemical composition, metal content and health risk assessment information of the herbal concoctions by informing safe usage and contributing to evidence based ethno-pharmacological research. The study provides an insight on the properties of bioactive compounds present in the herbal concoctions and emphasizes the necessity of continuous quality monitoring and chemical validation of traditional herbal mixtures to inform regulatory frameworks and public health policy.